Different healthy habits between northern and southern Spanish school children - Arriscado Alsina, Daniel; Knox, Emily; Zebala, Mikel; Dalmau, José María; Muros, José Joaquín (Journal of Public Health, 2018)
Aim Healthy habits are influenced by several factors such as geographical location. The aims of this study were to describe and compare healthy habits within two populations of sixth-grade primary school children (aged 11–12 years) from northern and southern Spain. Subjects and methods A cross-sectional study using two representative samples of school children was conducted. Participants came from Logroño (n = 329) in the north and Granada (n = 284) in the south of Spain. Socio-demographic and anthropometric variables, adherence to the Mediterranean diet, aerobic fitness, and healthy lifestyles were recorded. Results Boys reported a higher level of physical activity and aerobic fitness than girls (p = 0.000). Southern school children reported significantly higher adherence to the Mediterranean diet (♀: p = 0.041; ♂: p = 0.008), lower aerobic fitness (♀: p = 0.000; ♂: p = 0.042) and hours of nightly sleep (♀: p = 0.008, ♂: p = 0.007) than northern school children. Southern boys also reported lower levels of physical activity (p = 0.013). There were slight or moderate correlations among all habits measured (physical activity, diet, screen and sleep time). Additionally, the physical activity level was inversely related to weight status. Overweight and obese northern boys reported less physical activity than healthy-weight northern boys (p = 0.020) and overweight and obese southern girls reported less physical activity than healthy-weight southern girls (p = 0.024). Conclusions Results showed differences in physical activity, eating and sleep habits, and aerobic fitness according to geographical location. The relationships found among lifestyle habits indicate the need for health promotion interventions nationally and considering the differences discussed here.
Keywords: children; healthy habits; geographical location; Spain; Scopus; Emerging